Agrihydrobusiness in Uruguay: land grabbing, agrarian intensification, and water appropriation - Díaz Isasa, Ismael; Schiavone Cardoso, Eduardo (Geografares, 2025)
Water grabbing is a global issue, and the unequal appropriation of water is an emerging topic in Uruguay. This paper analyzes the pathways of water appropriation in rural territories of Uruguay and discusses the existence of water grabbing processes by examining agrarian intensification, land grabbing, and the construction of reservoirs for irrigation. A review of background studies and the processing of official data was conducted to characterize agrarian transformations. In addition, remote sensing techniques were used to georeference reservoirs, and geographic information systems were employed to analyze spatial relationships with agrarian variables. The results show an increase in the appropriation of green and blue water, along with an increase in gray water and international flows of virtual water. These increments, together with recent modifications in irrigation regulations, constitute the prelude to water grabbing in Uruguay.
Keywords: agribusiness; water footprint; irrigation